Misaligned environmental governance indicators and the mismatch between government actions and positive environmental outcomes. Issue 112 (October 2020) - Pillay, Yoganathan P.; Buschke, Falko T.
Highlights: The state of the environment keeps declining, despite increased government efforts. We ask if this is caused by governance indicators that measure effort and efficiency, rather than effectiveness. We categorise governance indicators in the South African environmental sector according to a causal logic model. Most governance indicators are at the wrong level of the logic model and do not measure government effectiveness as intended. This may explain why the state of environment keeps declining even when government consistently meets performance targets. Abstract: The state of the environment continues declining despite improved global responses towards environmental protection. This mismatch could be because government policymakers and bureaucrats tend to focus on the tangible and controllable aspects of interventions – such as resources and actions – rather than the consequences of these interventions. We test this assumption by classifying governance indicators in the environmental sector according to a logic model: an evidence-based causal chain articulating the causes, effects and consequences of management interventions. In this paper, we synthesized consensus on logic models and developed a decision tree to classify governance indicators depending on whether they measured inputs, activities, outputs, outcomes and impacts . We then applied this decision tree to indicators from the South African government's national environmental outcomes delivery agreement and found that environmental governance indicators tended to be at the activity or output levels. The shortage of indicators at the outcome level may explain why the state of the environment continues declining despite the environmental sector consistently meeting governance targets. Inappropriately aligned environmental governance indicators mean that officials work on interventions without knowing whether these are effective or not. Therefore, the environmental sector should prioritise the monitoring of the effectiveness of government interventions, rather than the interventions themselves.